Modeling and Simulation of Sierpinski Pentagon Fractal Antennas - Muhi, Malek A H; Habeeb, Mohammed A Z (Al-Nahrain Journal of Science, 2018)
Measurements of fractal shaped antennas are not enough to understand their physical behavior and there are antenna characteristics that can not be obtained by present day measurement techniques. Therefore, in the present work, the Ansoft HFSS finite element electromagnetic computer package was used to model, simulate and analyze the Sierpinski pentagon monopole microstrip patch fractal antenna and its complementary. The simulation results for both antennas show good matching with their feeds in the frequency range (2 GHz–12 GHz) and indicate that they can operate in the UMTS (2000 MHz–2200 MHz), Bluetooth (2400 MHz–2480 MHz), WLAN (2.4 GHz) and HIPERLAN (5.2 GHz) bands. Also, the computed results show, in general, good agreement with measured data for the S-parameter and radiation patterns.